Porter's ‘competitive advantage of nations’: An assessment - Grant, Robert M. (Strategic Management Journal, 1991)
Abstract Porter's Competitive Advantage of Nations is an important book which bridges the gap between strategic management and international economics while contributing substantially to both. Porter's analysis of the impact of national environment on international competitive performance demonstrates the potential for the theory of competitive strategy to rescue international economics from its slide into refined irrelevance, while simultaneously broadening the scope of the theory of competitive strategy to encompass both the international dimension and the dynamic context of competition. Nevertheless, the breadth and relevance of Porter's analysis have been achieved at the expense of precision and determinancy. Concepts are often ill defined, theoretical relationships poorly specified, and empirical data chosen selectively and interpreted subjectively.